If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7=(3x+9)+7
We simplify the equation to the form, which is simple to understand
7=(3x+9)+7
Remove unnecessary parentheses
7=3x+9+7
We move all terms containing x to the left and all other terms to the right.
-3x=+9+7-7
We simplify left and right side of the equation.
-3x=+9
We divide both sides of the equation by -03 to get x.
x=-3
| A^3+2a-25a-5/a-5 | | 525+0.21m=85 | | 120=w+41 | | -5/6-4/15 | | 525+0.21m=585+0.13m | | 711=q-800 | | A^3+2a-25a-50=0 | | 59+m=258 | | 7-4x= | | 5x-5(9x+11)=25 | | g+720=159 | | 23+b=75 | | .6=.30n | | .6=.3on | | 8x+8(-7-1x)=24 | | z-712=54 | | 210+0.25x=435 | | s+841=1000 | | 5a^2-26ab-24b^2=0 | | -20.7=-3.2+u/7 | | 34x^2-14=(7x+3)(14x-6) | | 2x^2y-2xy-12y= | | 4(2x-3)=3x-2 | | (x-6)(x+9)=x^2 | | 16=n-125 | | 3/4t-2=7 | | (x-6)(x+9)=2x | | X^2+6x+8=0 | | A=zw+z | | -8x^2+9x+7=0 | | p-7=3 | | mn-2p=2 |